Potent single-domain antibodies that arrest respiratory syncytial virus fusion protein in its prefusion state - Iebe Rossey; Morgan S. A. Gilman; Stephanie C. Kabeche; Koen Sedeyn; Daniel Wrapp; Masaru Kanekiyo; Man Chen; Vicente Mas; Jan Spitaels; José A. Melero; Barney S. Graham; Bert Schepens; et al. (Nature Communications, 2017)
Neutralizing antibodies for respiratory syncytial virus (RSV) can reduce disease in hospitalized children, but current options show limited efficacy. Here, the authors isolate potent single-domain antibodies from llamas that recognize the prefusion conformation of RSV F and prevent RSV replication in mice.